The impact of chronic heart failure on misinterpretation and misclassification of chronic obstructive pulmonary disease severity - Vyshnyvetskyy, I.I.; Borovtsova, A. Yu. (Zaporozhye Medical Journal, 2016)
Aim. To evaluate the impact of comorbid chronic heart failure (CHF) on the severity of symptoms and correctness of chronic obstructive pulmonary disease (COPD) classification. Materials and methods. Cross-sectional study included 177 patients with COPD and concomitant cardiovascular diseases. All patients were undergone spirometry, chest radiography, echocardiography, validated questionnaires (COPD assessment test (CAT), Hospital anxiety and depression scale (HADS)). Multiple regression was used to establish adjusted impact of CHF presence on CAT scores and COPD severity misclassification. Results. It was established that the presence of comorbid CHF increases CAT score by 3.29, 95% CI [1.71–5.02] points. In the overall cohort of COPD patients CAT scores adjustment for the presence of CHF has resulted in reclassification of 15.5% of patients from group B to group A, and 4.3% of patients from group D to group C. Among selective patients with COPD and CHF the rate of revised classification constituted 32.1% and 7.9%, respectively. Conclusion. The presence of comorbid CHF is able to significantly change the correct assessment of the intensity of COPD symptoms, disease-specific health status and classification of COPD severity.